Diffusion of Alkali Metals in Polycrystalline CuInSe2and Their Role in the Passivation of Grain Boundaries - Chugh, Manjusha; Kühne, Thomas D.; Mirhosseini, Hossein (ACS Applied Materials and Interfaces, 2019)
The behavior of alkali atom point defects in polycrystalline CuInSe 2 is studied. In this work, three grain boundary models, one coherent twin boundary and two twin boundaries with dislocation cores, are considered. Total energy calculations show that all alkali metals tend to segregate at the grain boundaries. In addition, the segregation of alkali atoms is more pronounced at the grain boundaries with the dislocation cores. The diffusion of alkali metals along and near grain boundaries is studied as well. The results show that the diffusion of alkali atoms in the grain boundary models is faster than within the bulk. In addition, the ion exchange between Na and Rb atoms at the grain boundaries leads to the Rb enrichment at the grain boundaries and the increase of the Na concentration in the bulk. While the effects of Na and Rb point defects on the electronic structure of the grain boundary with the anion-core dislocation are similar, Rb atoms passivate the grain boundary with the cation-core dislocation more effectively than Na. This can explain the further improvement of the solar cell performance after the RbF-postdeposition treatment.
CRIS-Team Scopus Importer:2023-03-20
Keywords: CuInSe; diffusion mechanisms; grain boundary passivation; thin-film solar cells